2005
DOI: 10.1111/j.1529-8817.2005.04124.x
|View full text |Cite
|
Sign up to set email alerts
|

SEX‐SPECIFIC CELL SURFACE STRUCTURE OF ANISOGAMETES: MORPHOLOGICAL CHANGES DURING FERTILIZATION OF BRYOPSIS MAXIMA (ULVOPHYCEAE, CHLOROPHYTA) REVEALED BY ULTRA–HIGH‐RESOLUTION FIELD EMISSION SEM1

Abstract: Cell surfaces of biflagellate gametes and their morphological changes during fertilization of Bryopsis maxima Okamura were observed using a high-resolution field emission scanning electron microscope. Male gametes have broad and narrow faces, which are divided into at least five morphologically distinct regions: 1) the apical plate is a plate-like structure that is approximately 380-530 nm long and approximately 190 nm wide, in the center of the papilla and slightly protruded from the plasma membrane; 2) strip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…1A,B). Furthermore, in cases where only the female gamete has an eyespot, such as those of anisogametes of caulerpalean algae Bryopsis maxima Okamura (Hori 1988; Miyamura et al . 2005) and Caulerpa racemosa var.…”
Section: Introductionmentioning
confidence: 99%
“…1A,B). Furthermore, in cases where only the female gamete has an eyespot, such as those of anisogametes of caulerpalean algae Bryopsis maxima Okamura (Hori 1988; Miyamura et al . 2005) and Caulerpa racemosa var.…”
Section: Introductionmentioning
confidence: 99%
“…in C. reinhardtii and G. pectorale, while they were inherited from female gametes (MID-) in V. carteri (Table 3). Table 3 Relationship between the transmission patterns of organelle genomes and the sex-specific features in green plants indicates the results of MGEC2 9 MGEC5 d 1, Sager (1954); 2, Boynton et al (1987); 3, Holmes and Dutcher (1989); 4, Ferris and Goodenough (1994); 5, Mori et al (2006); 6, Liu et al (2008);7, Hamaji et al (2008); 8, Adams et al (1990); 9, Miyamura (2003); 10, Kagami et al (2008); 11, Mogi et al (2008); 12, Kawano (2008); 13, Kuroiwa et al (1991); 14, Miyamura et al (2005); 15, Miyamura and Nagumo (2007); 16, Miyamura and Hori (1997); 17, Mori et al (2006); 18, Miyamura et al (1987); 19, Kirk and Tilney-Bassett (1978) Hamaji et al (2008) suggested that the patterns of mitochondrial inheritance changed at some point during the evolution of colonial Volvocales from uniparentally from the MID-containing parent (MID?) to uniparentally from the female (MID-).…”
Section: Digestion Of Organelle Dna and Disintegration Of Organelles mentioning
confidence: 95%
“…The present study is intended to clarify such aspects of planozygote behavior using a siphonous green alga, B. maxima . Figure 1 portrays a schematic drawing of the biflagellate gametes and quadriflagellate planozygote representing the spatial relationship between the male and female flagella based on their ultrastructure (Hori 1988; Miyamura et al . 2005).…”
Section: Introductionmentioning
confidence: 99%
“… Schematic diagram of the mating male and female gametes and planozygote of Bryopsis maxima based on observations of previous (Hori 1988; Miyamura et al . 2005) and present studies.…”
Section: Introductionmentioning
confidence: 99%